The Eleventh Marcel Grossmann Meeting 2008
DOI: 10.1142/9789812834300_0327
|View full text |Cite
|
Sign up to set email alerts
|

Transient Chaos in Scalar Field Cosmology on a Brane

Abstract: We study cosmological dynamics of a flat Randall-Sundrum brane with a scalar field and a negative "dark radiation" term. It is shown that in some situations the "dark radiation" can mimic spatial curvature and cause a chaotic behavior which is similar to chaotic dynamics in closed Universe with a scalar field.The phenomenon of transient chaos in homogeneous cosmological models had been described by D. Page [1] (he studied a closed isotropic Universe with a massive scalar field) even earlier than this concept w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In a general situation this behavior exists even for quadratic potential if the constant C from the constraint equation (5) is sufficiently large and negative. In nonstandard cosmology this type of dynamics exists also in braneworlds [9] and in theories with quadratic curvature corrections to Einstein gravity [10]. It has been already reported that in these two cases the picture of chaotic dynamics changes significantly in comparison with the case of massive scalar field [7,12].…”
mentioning
confidence: 87%
“…In a general situation this behavior exists even for quadratic potential if the constant C from the constraint equation (5) is sufficiently large and negative. In nonstandard cosmology this type of dynamics exists also in braneworlds [9] and in theories with quadratic curvature corrections to Einstein gravity [10]. It has been already reported that in these two cases the picture of chaotic dynamics changes significantly in comparison with the case of massive scalar field [7,12].…”
mentioning
confidence: 87%
“…In nonstandard cosmology this type of dynamics exists also in braneworlds[19] and in theories with quadratic curvature corrections to Einstein gravity[20].…”
mentioning
confidence: 98%